2020
DOI: 10.1111/1748-5967.12461
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of GM and non‐GM soybean varieties on non‐target arthropods

Abstract: In order to guarantee the safety of genetically modified (GM) soybean crops, it is important to assess the potential toxicity of their expressed insecticidal proteins to non-target organisms. In the present study, the effects of the GM soybean Insulin-like Growth Factor (IGF), which is tolerant to the herbicide glufosinate, on plant-dwelling non-target insects and arachnids were evaluated in soybean agroecosystems. For comparison, the non-GM parental cultivar of soybean Gwangan-kong was used as a control. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Moreover, no differences in life cycle or behaviour in comparison to individuals fed on non-Bt-fed prey were detected. Considering the environmental risk assessment in other Bt crops, no negative effects were observed for predatory staphylinids in transgenic rice (with Cry1Aa protein) [28], and similarly, no toxic effects were observed in transgenic soybean to different non-target arthropods [29]. Twardowski et al [9], in the experiment conducted in Poland, found no significant effects of Bt-maize on ground beetles, which are also epigeic predators.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no differences in life cycle or behaviour in comparison to individuals fed on non-Bt-fed prey were detected. Considering the environmental risk assessment in other Bt crops, no negative effects were observed for predatory staphylinids in transgenic rice (with Cry1Aa protein) [28], and similarly, no toxic effects were observed in transgenic soybean to different non-target arthropods [29]. Twardowski et al [9], in the experiment conducted in Poland, found no significant effects of Bt-maize on ground beetles, which are also epigeic predators.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings supported the results of the previous findings where a higher occurrence of insects was found in the soybean field of Ochang than Jeonju, and also no harmful impact of IGF (Insulin‐like Growth Factor) soybean on arthropods over the non-GM soybean was indicated. 8 …”
Section: Discussionmentioning
confidence: 99%
“…According to research reports, GM soybean IGF and TRX did not affect arthropod diversity over non-GM soybean. 8 , 9 Several other studies investigated the safety of the non-target arthropod populations in the presence of transgenic Bt proteins in cotton, maize and soybean, and reported their negligible short-term impact on them. 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the positive aspects of GM crops, many concerns such as potential toxicities and allergies, gene flow, weeds, generation of new types of toxins and viruses, disruption to ecosystems, and environmental impacts are also emerging (Oh et al 2016b). In response to these concerns, Korean studies are evaluating the safety of GM crops, with emphasis on biodiversity research through quantitative studies of species, population changes, and surrounding ecosystems (Amin et al 2020;Choi et al 2015;Kwon 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In response to these concerns, Korean studies are evaluating the safety of GM crops, with emphasis on biodiversity research through quantitative studies of species, population changes, and surrounding ecosystems (Amin et al . 2020; Choi et al . 2015; Kwon 2008).…”
Section: Introductionmentioning
confidence: 99%